Academic use of engineering students in first semester systems - Alcivar, Ruben Dario Basurto; Ormaza, Gema Monserrate Flores (International Journal of Social Sciences and Humanities, 2018)
The use of learning strategies facilitates the student's formative process, achieving deep learning related to academic performance. The low amount of work on the learning techniques used by students in engineering training contexts was the motivation to carry out this descriptive exploratory study. The level of utilization of learning skills was investigated to 145 first-semester students, taking into account the academic history of the participants and their availability of time to study, assessing the difference in the use of the different study methods. The data on the use of the learning techniques were obtained through the strategy and motivation questionnaire, which was collected with populations of two academic sections, in the year 2017 and 2018. The corresponding statistical analyzes were carried out that allowed having the results according to the effort made, the economic and social characteristics of each student; the design and results of this research explain the levels of use of learning tactics of participating students; It also allows creating the bases to design future educational interventions in order to promote among students the use of learning skills.